2014
DOI: 10.1007/s10571-014-0058-5
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic Subependymal Niche: A Novel Site of the Adult Neurogenesis

Abstract: The discovery of undifferentiated, actively proliferating neural stem cells (NSCs) in the mature brain opened a brand new chapter in the contemporary neuroscience. Adult neurogenesis appears to occur in specific brain regions (including hypothalamus) throughout vertebrates’ life, being considered an important player in the processes of memory, learning, and neural plasticity. In the adult mammalian brain, NSCs are located mainly in the subgranular zone (SGZ) of the hippocampal dentate gyrus and in the subventr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 115 publications
(154 reference statements)
0
56
1
1
Order By: Relevance
“…The structure of the neurogenic niche in the hypothalamus is quite well investigated [3,8,45] and now we are aware of some endogenous regulators of this sophisticated phenomenon [10][11][12][13]47]. Different studies have also tried to identify the exact origin of newborn cells in the hypothalamus, which led to the discovery of many subsets of tanycytes -radial glia cells located mainly along the brain third ventricle [47,48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The structure of the neurogenic niche in the hypothalamus is quite well investigated [3,8,45] and now we are aware of some endogenous regulators of this sophisticated phenomenon [10][11][12][13]47]. Different studies have also tried to identify the exact origin of newborn cells in the hypothalamus, which led to the discovery of many subsets of tanycytes -radial glia cells located mainly along the brain third ventricle [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…However, the presence of established and permanently functional neural stem cells (NSCs) niches in the aforementioned brain areas is still quite controversial. A hypothesis suggesting existence of a stable hypothalamic neurogenic site located in the subependymal zone of the third ventricle (hypothalamic ventricular zone, HVZ) seems to be especially intriguing and relatively well-documented [1,8]. More importantly, it is also suggested that hypothalamic neurogenesis is significantly involved in various regulatory mechanisms, particularly in energy balance regulation [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The ependymal cells in the walls of the 3rdV in contact with the CSF are ciliated. Collectively, these ependymal cells form a barrier of tight junctions between the brain parenchyma and CSF in the lumen of the 3rdV (Rojczyk‐Gołębiewska et al ., ). The walls of the 3rdV also are lined by an abundance of specialized ependymal cells called tanycytes, which have a cell soma in the ventricular wall and a distal process contacting the portal vessels (Millhouse, ; Bruni et al ., ; Langlet et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the rodent SVZ has been thoroughly investigated, less attention has been given to other regions of the ventricular system, including the 3rdV, and to whether cells residing in the walls of the 3rdV can function as neural progenitor cells in vivo (Bruni, 1998;Rojczyk-Gołe z biewska et al, 2014;Goodman & Hajihosseini, 2015;Maggi et al, 2015;Chaker et al, 2016). The 3rdV is a narrow cleft-like channel in the diencephalon of the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Radiation has been linked to anorexia in humans (25), but since we did not track food consumption, no conclusions can be drawn regarding the contribution of anorexia to the differences in weight gain. Hypothalamic neurogenesis may regulate eating behavior and weight loss in mice (26). However, neurogenesis in other brain areas is susceptible to radiation doses as low as 5 Gy (27); thus, it is unlikely that our fractionated paradigm would have sufficiently spared hypothalamic neurogenesis to contribute to the weight gain differences.…”
Section: Discussionmentioning
confidence: 99%